Livsmanualernes popularitet – Hvorfor Covey’s vaneparadigme blev populært i 1990’erne - Christensen, Christian Olaf (Slagmark - Tidsskrift for idéhistorie, 2018)
This article examines the popularity of Stephen Covey’s theory of selfmanagement and habits. It argues that changes in the economic context have been decisive for the recent renaissance of a character ethic. The article locates Covey’s theory in its American intellectual and economic context, arguing that especially Benjamin Franklin’s autobiography and Viktor Frankl’s logotherapy constitute key influences on Covey’s work. Covey articulates a seducing rhetorical vision of personal and organisational growth. It fits well into a neo-liberal political and economic context in which individual responsibility is stressed. However, critics rightfully argue that it has little to say about structural problems of social and economic systems, and that it exaggerates individuals’ capabilities.